2022
DOI: 10.3390/ma15165513
|View full text |Cite
|
Sign up to set email alerts
|

N′-Substituted 4-Phenylpicolinohydrazonamides with Thiosemicarbazone Moiety as New Potential Antitubercular Agents: Synthesis, Structure and Evaluation of Antimicrobial Activity

Abstract: Three new 4-phenylpicolin derivatives with a thiosemicarbazone structure were synthesized and evaluated for tuberculostatic activity. The compounds were obtained by the condensation of methyl 4-phenylpicolonimidate with the corresponding cycloalkylamino-1-carbothiohydrazides. The 1H NMR temperature spectra obtained showed proton lability at the nitrogen atom N2, and X-ray crystallography confirmed the zwitterionic structure of all products. ADME calculations indicate that the compounds can be tested as future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the crystal structure of 6, the phenyl group is not coplanar with the furan ring, as evidenced by the dihedral angle of 2.56 (8) °and by the torsion angles C1-C6-C7-O1: 25.1(2) and C1-C6-C7-C8: −148.4(2) °. However, for 7 and 8 the presence of the fuoro and methoxy substituent groups attached to the C2′ and C4′ carbons of the phenyl fragment cause a certain coplanarity with the furan ring, being demonstrated by the dihedral angles of 13.53 (9) °in 7 and 3.47 (6) °in 8 (Table S1, supplementary material) as well as by the torsion angles C1-C6-C7-O1: 172.6(1) and C5-C6-C7-O1: 10.6(2) °for 7, and C1-C6-C8-O2: −3.6(2) and C5-C6-C8-O2: 177.2(1) °for 8. In all studied crystal structures, the furan ring is coplanar with the thiosemicarbazone fragment within a deviation of ±11 °.…”
Section: X-ray Difractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the crystal structure of 6, the phenyl group is not coplanar with the furan ring, as evidenced by the dihedral angle of 2.56 (8) °and by the torsion angles C1-C6-C7-O1: 25.1(2) and C1-C6-C7-C8: −148.4(2) °. However, for 7 and 8 the presence of the fuoro and methoxy substituent groups attached to the C2′ and C4′ carbons of the phenyl fragment cause a certain coplanarity with the furan ring, being demonstrated by the dihedral angles of 13.53 (9) °in 7 and 3.47 (6) °in 8 (Table S1, supplementary material) as well as by the torsion angles C1-C6-C7-O1: 172.6(1) and C5-C6-C7-O1: 10.6(2) °for 7, and C1-C6-C8-O2: −3.6(2) and C5-C6-C8-O2: 177.2(1) °for 8. In all studied crystal structures, the furan ring is coplanar with the thiosemicarbazone fragment within a deviation of ±11 °.…”
Section: X-ray Difractionmentioning
confidence: 99%
“…Tese compounds which contain N and S atoms usually act as bidentate or multidentate chelating ligands and can coordinate to transition metal ions through the sulfur and hydrazine nitrogen atoms [1]. Extensive investigations conducted by researchers have demonstrated that metal complexes with some thiosemicarbazone derivatives present a wide range of biological applications, such as antibacterial [2,3], antifungal [1,4], antiparasitic [5], antitubercular [6,7], antiviral [8,9], antioxidant [10,11], and antitumoral activities [12][13][14].…”
Section: Introductionmentioning
confidence: 99%